2016
DOI: 10.18632/oncotarget.10318
|View full text |Cite
|
Sign up to set email alerts
|

Class A1 scavenger receptor modulates glioma progression by regulating M2-like tumor-associated macrophage polarization

Abstract: Macrophages enhance glioma development and progression by shaping the tumor microenvironment. Class A1 scavenger receptor (SR-A1), a pattern recognition receptor primarily expressed in macrophages, is up-regulated in many human solid tumors. We found that SR-A1 expression in 136 human gliomas was positively correlated with tumor grade (P<0.01), but not prognosis or tumor recurrence. SR-A1-expressing macrophages originated primarily from circulating monocytes attracted to tumor tissue, and were almost twice as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…While it is well documented that GAMs have an M2-like phenotype ( 37 , 38 , 46 , 47 ), the majority of data did not compare tumors longitudinally to understand whether GAMs begin as M2-like or whether there is a phenotypic shift. Our longitudinal clinical data confirm that GAMs assume a classically activate M1 phenotype early on in tumor growth and as the tumor progresses to a more advanced stage, these GAMs switch to resemble an alternatively activated M2 phenotype ( 48 , 49 ). This has now been shown to be related to the level of hypoxia within the tumors ( 50 52 ).…”
Section: Discussionsupporting
confidence: 65%
“…While it is well documented that GAMs have an M2-like phenotype ( 37 , 38 , 46 , 47 ), the majority of data did not compare tumors longitudinally to understand whether GAMs begin as M2-like or whether there is a phenotypic shift. Our longitudinal clinical data confirm that GAMs assume a classically activate M1 phenotype early on in tumor growth and as the tumor progresses to a more advanced stage, these GAMs switch to resemble an alternatively activated M2 phenotype ( 48 , 49 ). This has now been shown to be related to the level of hypoxia within the tumors ( 50 52 ).…”
Section: Discussionsupporting
confidence: 65%
“…The proposed mechanisms of action involve interrupting TAM/cancer cell crosstalk, blocking SR-A1 from scavenging ECM components that allow for cancer cell migration, and scavenging of pro-inflammatory/angiogenic lysophosphatidic acid (LPA) [151]. However, in the context of glioma model, Zhang et al demonstrated that recognition of tumor-secreted heat shock protein 70 (HSP70) by SR-A1 is important in suppressing M2 polarization in TAMs and is needed for inhibition of glioma proliferation and angiogenesis [152]. These studies highlight the context-dependent effect in modulation of scavenger receptor activity as a result of its recognition of a broad range of ligands.…”
Section: Pharmacological Modulation Of Macrophages/tamsmentioning
confidence: 99%
“…STAT3 activation in tumor-associated macrophages (TAMs) has also been associated with their acquirement of pro-tumorigenic features. In a rat model of breast cancer, STAT3 inhibition could revert a TAM immune suppressing phenotype leading to immune-mediated inhibition of tumor growth [133], and STAT3 was shown to promote pro-tumorigenic M2 polarization of TAMs in glioma, enhancing proliferation and angiogenesis [134]. This activity may be due to STAT3mediated expression of the B7-H4 T-cell co-inhibitory molecule that impairs CD8 + T cell activation [135].…”
Section: Tumor Associated Macrophages (Tams)mentioning
confidence: 99%